2018
DOI: 10.1007/s11661-018-4911-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Deformation of Metastable Austenitic Stainless Steels at the Nanometric Length Scale

Abstract: Cyclic indentation was used to evaluate the dynamic deformation on metastable steels, particularly in an austenitic stainless steel, AISI 301LN. In this work, cyclic nanoindentation experiments were carried out and the obtained loading-unloading (or P-h) curves were analyzed in order to get a deeper knowledge on the time-dependent behavior, as well as the main deformation mechanisms. It was found that the cyclic P-h curves present a softening effect due to several repeatable features (pop-in events, ratcheting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
2
0
1
Order By: Relevance
“…Laplanche et al suggested the occurrence of twin formation and phase transformation in NiTi alloys [ 220 ]. The phase-transformation-induced plasticity (TRIP) effect is expected to be a novel idea for obtaining a better performance in strength–ductility balance in steel, and many studies have approached this behavior by indentation [ 222 , 223 , 224 , 225 , 226 , 227 , 228 , 229 ]. Lu et al analyzed the indentation-induced mechanical behavior of retained austenite in a bearing steel [ 222 ].…”
Section: Other Mechanisms Of the Eventmentioning
confidence: 99%
“…Laplanche et al suggested the occurrence of twin formation and phase transformation in NiTi alloys [ 220 ]. The phase-transformation-induced plasticity (TRIP) effect is expected to be a novel idea for obtaining a better performance in strength–ductility balance in steel, and many studies have approached this behavior by indentation [ 222 , 223 , 224 , 225 , 226 , 227 , 228 , 229 ]. Lu et al analyzed the indentation-induced mechanical behavior of retained austenite in a bearing steel [ 222 ].…”
Section: Other Mechanisms Of the Eventmentioning
confidence: 99%
“…En etapas posteriores, el aumento de la densidad de dislocaciones puede presentarse en granos orientados con deslizamiento múltiple, en la formación de arreglos subestructurales como canales y estructuras celulares. Roa et al [3] encontraron que la transformación martensítica ocurre en aceros austeníticos metaestables bajo carga cíclica en amplitudes de tensión/deformaciones significativamente más bajas que el valor límite requerido en caso de carga monotónica.…”
Section: Introductionunclassified
“…Following these ideas, an extensive program comprised of different nanoindentation experiments was developed by the authors in order to deform metastable steel samples in a controlled way. Thus, the dynamic deformation was examined by means of cyclic nanoindentation, concluding that metastable stainless steels present an inelastic nature of the unloading/reloading response which is mainly related to the ratcheting effect [14]. The influence of testing mode on the fatigue behavior was also studied, and the results showed that nanoindentation under loading control mode could be compared to conventional low-cycle fatigue tests, whereas the experiments performed under displacement control mode may be associated with high-cycle fatigue tests [15].…”
Section: Introductionmentioning
confidence: 99%